A népesség számának, összetételének és területi eloszlásának változása Debrecenben 1939 és 1990 között - Kozma, Gábor (Tér és Társadalom, 1996)
The changes in our big cities after the World War II. made radical changes in the spatial structure of the city, the distribution of population, the alter of it's main characteristics. This study shows the most important processes in Debrecen, between 1939 and 1990. The analysis contenrated to the inner-city area, which divided into 42 parts, all of them whith unique specifics. The population growth, the decreption, the tertiarisation formed characteristic spatial types inside the city. If we can collect and analyse the main phenomenons in the last half century we can understand the most important processes in the part, present and the near future, too.